2020
DOI: 10.1093/mnras/staa551
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the spatial distribution and kinematics of globular clusters within galaxy clusters in illustris

Abstract: We study the assembly of globular clusters (GCs) in 9 galaxy clusters using the cosmological simulation Illustris. GCs are tagged to individual galaxies at infall time and their tidal removal and distribution within the cluster is followed later self-consistently by the simulation. The method relies on the simple assumption of a single power-law relation between halo mass (M vir ) and mass in GCs (M GC ) as found in observations. We find that the GCs specific frequency S N as a function of V-band magnitude nat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 123 publications
2
18
0
Order By: Relevance
“…It may soon be possible to do galactic archaeology with GCs by using the current properties of GC systems (such as masses, ages, metallicities, and kinematics) to infer the environmental conditions in their progenitor galaxies at the time of their formation. Recent works have used particle tagging or analytical cluster models (Kruijssen 2015;Reina-Campos & Kruijssen 2017) and their implementation into fully cosmological galaxy formation simulations to make important steps towards this goal (Renaud et al 2017;Pfeffer et al 2018;Kruijssen et al 2019a,b;Ramos-Almendares et al 2020;Halbesma et al 2020;Kruijssen et al 2020). Semianalytic GC formation models are now able to predict the GC mass, metallicity, and age distribution of large statistical samples of galaxies in DM-only cosmological simulations (Choksi et al 2018;Choksi & Gnedin 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It may soon be possible to do galactic archaeology with GCs by using the current properties of GC systems (such as masses, ages, metallicities, and kinematics) to infer the environmental conditions in their progenitor galaxies at the time of their formation. Recent works have used particle tagging or analytical cluster models (Kruijssen 2015;Reina-Campos & Kruijssen 2017) and their implementation into fully cosmological galaxy formation simulations to make important steps towards this goal (Renaud et al 2017;Pfeffer et al 2018;Kruijssen et al 2019a,b;Ramos-Almendares et al 2020;Halbesma et al 2020;Kruijssen et al 2020). Semianalytic GC formation models are now able to predict the GC mass, metallicity, and age distribution of large statistical samples of galaxies in DM-only cosmological simulations (Choksi et al 2018;Choksi & Gnedin 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Decades after the pioneering work of Searle & Zinn (1978) demonstrated the potential of GCs as tracers of galaxy formation, new studies began to exploit it (e.g. Côté, Marzke & West 1998;Bekki et al 2005;Rhode, Zepf & Santos 2005;Muratov & Gnedin 2010;Arnold et al 2011;Tonini 2013;Beasley et al 2018;Choksi, Gnedin & Li 2018;Fahrion et al 2020;Ramos-Almendares et al 2020). Theoretical studies of the formation and co-evolution of galaxies and GCs have shown that GCs trace the build-up of L * galaxies across cosmic time (Reina-Campos et al 2019), and that their abundances and ages contain a record of the assembly history of their host (Kruijssen et al 2019a, b;Massari et al 2019).…”
mentioning
confidence: 99%
“…The early quenching of DF44 (at z ∼ 1-2 based on its inferred stellar age) would naturally lead to a presentday GC system that is overpopulous, and a stellar-tohalo mass ratio (M * /M h ) that is unusually low, relative to more typical dwarfs with similar stellar masses but later quenching. Similar scenarios have previously been discussed in the context of dwarfs with high GC specific frequencies that fall into clusters early (Peng et al 2008;Liu et al 2016;Mistani et al 2016;Ramos-Almendares et al 2020), with recent work extending the concept to UDGs (Carleton et al 2020). However, DF44 was identified as a challenge to explain in this scenario, owing to its particularly high GC specific frequency, and here we also note that its late rather than early infall presents a fundamental distinction -requiring a noncluster quenching mechanism.…”
Section: The Evolutionary History Of Df44: Knowns and Unknownsmentioning
confidence: 53%